2018
DOI: 10.1002/glia.23573
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐targeted IL‐10 production decreases proliferation and induces a downregulation of activated microglia/macrophages after PPT

Abstract: When central nervous system (CNS) homeostasis is altered, microglial cells become rapidly activated, proliferate and release a broad range of molecules. Among the plethora of molecules involved in the regulation of microglial activation, cytokines are considered crucial. Although production of interleukin‐10 (IL‐10) has been demonstrated after different types of CNS injuries and associated with protective functions, the specific role played by IL‐10 modulating microglial cells remains unclear. Hence, the objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 72 publications
7
13
1
Order By: Relevance
“…Previous studies have also indicated that microglia is a major source of locally produced TGF-β after HI insult [63]. However, consistent with our findings, other cells have been reported to be produced after microglia depletion [64]. Taken together, our findings indicate that microglial depletion aggravates neuronal death due to a lack of anti-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have also indicated that microglia is a major source of locally produced TGF-β after HI insult [63]. However, consistent with our findings, other cells have been reported to be produced after microglia depletion [64]. Taken together, our findings indicate that microglial depletion aggravates neuronal death due to a lack of anti-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, IL-4 and IL-10, a product of macrophages, microglia and lymphocytes, once generated, inhibit the release of pro-inflammatory cytokines from the same cells, resulting in indirect downregulation of astrocyte reactivity (Harry and Kraft 2008). Moreover, alterations in brainderived IL-2 and IL-2 receptors, potentially produced by neurons and astrocytes (Shen et al 2010), have been implicated in the pathogenesis of several major neurological disorders due to their immunoregulatory functions (Wei et al 2014); among these, the ability to drive GFAP+ astrocyte-targeted production of IL-10, which in turn modulates the numbers of microglia/ macrophages, has been postulated (Recasens et al 2019). Therefore, it would be interesting to investigate whether opposite regulation of the identified signalling by functionally different cytokines might be involved in modulating astrocyte reactivity, especially when considering that neuroinflammation associated with neurodegenerative diseases (AD, PD, multiple sclerosis, amyotrophic lateral sclerosis and ischemia) constitutes a superimposed exacerbating factor.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐6, IL‐2, and IL‐4 were described in this article as modulatory cytokines because they may induce and terminate inflammatory responses depending on the context of inflammation (Hoyer, Dooms, Barron, & Abbas, ; Luzina et al, ; Rothaug, Becker‐Pauly, & Rose‐John, ). These three cytokines are able to modulate microglial function (Akhmetzyanova, Kletenkov, Mukhamedshina, & Rizvanov, ; Recasens, Shrivastava, Almolda, Gonzalez, & Castellano, ; Rossi et al, ) as well as astrocyte activation (Alves et al, ; Brodie, Goldreich, Haiman, & Kazimirsky, ; Klein et al, ). Diapedesis and activation of other immunocompetent cells like neutrophils and lymphocytes within the brain can also be regulated by these modulatory cytokines (Erta, Quintana, & Hidalgo, ; Gadani, Cronk, Norris, & Kipnis, ; Gao et al, ).…”
Section: Discussionmentioning
confidence: 99%